2004
DOI: 10.1017/s1041610204000079
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral symptoms and the administration of psychotropic drugs to aged patients with dementia in nursing homes and in acute geriatric wards

Abstract: Objectives:To describe the prevalence of various psychiatric and behavioral symptoms among patients with dementia in nursing homes and acute geriatric wards and to investigate the administration of psychotropic medications to these patients.Methods: 425 consecutive patients (>70 years) in six acute geriatric wards in two city hospitals and seven nursing homes in Helsinki, Finland, were assessed with an extensive interview, cognitive tests, and attention tests. Of these, 255 were judged to have dementia accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
58
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 27 publications
9
58
2
4
Order By: Relevance
“…The prevalence of antipsychotic medication in this study is in line with, or somewhat lower than, that reported previously (Craig et al, 2003;Pitkala et al, 2004;Sørensen et al, 2001). Different population characteristics and methodology make closer comparisons impossible.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The prevalence of antipsychotic medication in this study is in line with, or somewhat lower than, that reported previously (Craig et al, 2003;Pitkala et al, 2004;Sørensen et al, 2001). Different population characteristics and methodology make closer comparisons impossible.…”
Section: Discussionsupporting
confidence: 85%
“…These behaviors and psychological symptoms are very common in populations of old people with dementia and the prevalence of BPSD in different studies varies between 79% and approximately 92% (Brodaty et al, 2001;Margallo-Lana et al, 2001;Pitkala et al, 2004). Some of the symptoms increase the difficulty of caring for the person with dementia, and there is a correlation between BPSD and burden of care, and even with caregiver depression (Black and Almeida, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O encontro frequente de prescrições com neurolépticos também foi observado em outros estudos 16,17 , havendo predomínio do uso de neurolépticos atípicos, como observado na presente casuística. A relação entre demência e consumo de neurolépticos, fato usual em ILPI, é dado relatado com constância [18][19][20][21] . Estudos demonstram que os institucionalizados cursam com maior prevalência de depressão, levando a uma maior utilização de antidepressivos, podendo chegar a 31,0% em algumas casuísticas, número maior se comparado ao presente estudo 20,22 .…”
Section: Discussionunclassified
“…A relação entre demência e consumo de neurolépticos, fato usual em ILPI, é dado relatado com constância [18][19][20][21] . Estudos demonstram que os institucionalizados cursam com maior prevalência de depressão, levando a uma maior utilização de antidepressivos, podendo chegar a 31,0% em algumas casuísticas, número maior se comparado ao presente estudo 20,22 . Deve-se, porém, enfatizar que o encontro de 17,7% de prescrições com fármacos antidepressivos nesta casuística não deve ser considerado como menor, visto que praticamente um em cada cinco institucionalizados utilizava esse grupo medicamentoso.…”
Section: Discussionunclassified